(untitled) (REMUNOM, 2026)
Sustainable food consumption has gained prominence in academic and social discussions due to the environmental, social, and ethical challenges posed by current production and consumption patterns. From a theoretical perspective, the literature indicates that factors such as motivations, personal values, attitudes, and contextual barriers significantly influence sustainable food choices, supported by models such as the Theory of Planned Behavior and Schwartz’s Theory of Values, as well as approaches that consider the interaction between attitudes and contextual factors. Based on this framework, this study conducted a narrative review of national and international scientific production, encompassing both theoretical and empirical works addressing environmental concerns, measurement instruments, and behavioral explanations. The results indicate that although biospheric and altruistic values are directly associated with the adoption of sustainable food practices, obstacles such as high prices, limited access, and unclear communication of sustainability attributes hinder the effective consolidation of these choices. Conversely, factors such as increased perceived consumer efficacy, clearer and more transparent communication strategies, and educational campaigns contribute to reducing the gap between attitudes and behavior. The discussion highlights the need to integrate social and ethical dimensions of sustainability, as well as to consider cultural specificities, particularly the Brazilian context, which remains underexplored in the literature. It is concluded that advancing knowledge on sustainable food consumption requires integrated theoretical approaches and initiatives that foster more responsible food choices, providing support for future research and for the development of policies and strategies aimed at promoting sustainable consumption.